Longitudinal pathways of exclusive and polytobacco cigarette use among youth, young adults and adults in the USA: findings from the PATH Study Waves 1–3 (2013–2016). (22nd April 2020) - Taylor, Kristie A; Sharma, Eva; Edwards, Kathryn C; Halenar, Michael J; Kissin, Wendy; Kasza, Karin A; Day, Hannah; Anic, Gabriella; Gardner, Lisa D; Hammad, Hoda T; Hull, Lynn C; Bansal-Travers, Maansi; et al.
Abstract : Objective: Cigarettes are the most harmful and most prevalent tobacco product in the USA. This study examines cross-sectional prevalence and longitudinal pathways of cigarette use among US youth (12–17 years), young adults (18–24 years) and adults 25+ (25 years and older). Design: Data were drawn from the first three waves (2013–2016) of the Population Assessment of Tobacco and Health Study, a nationally representative, longitudinal cohort study of US adults and youth. Respondents with data at all three waves (youth, N=11 046; young adults, N=6478; adults 25+, N=17 188) were included in longitudinal analyses. Results: Among Wave 1 (W1) any past 30-day (P30D) cigarette users, more than 60%, persistently used cigarettes across three waves in all age groups. Exclusive cigarette use was more common among adult 25+ W1 P30D cigarette users (62.6%), while cigarette polytobacco use was more common among youth (57.1%) and young adults (65.2%). Persistent exclusive cigarette use was the most common pathway among adults 25+ and young adults; transitioning from exclusive cigarette use to cigarette polytobacco use was most common among youth W1 exclusive cigarette users. For W1 youth and young adult cigarette polytobacco users, the most common pattern of use was persistent cigarette polytobacco use. Conclusions: Cigarette use remains persistent across time, regardless of age, with most W1 P30D smokers continuing to smoke at all three waves. Policy efforts need to continue focusing on cigarettes, in addition to products such as electronic nicotine delivery systems that are becoming more prevalent.